Post-marketing surveillance of adverse events following measles, mumps, rubella and varicella (MMRV) vaccine: retrospecive study in apulia region (ITALY), 2009-2017 - Pasquale Stefanizzi; Sara De Nitto; Francesco Patano; Francesco Paolo Bianchi; Davide Ferorelli; Paolo Stella; Domenica Ancona; Vito Bavaro; Silvio Tafuri (Taylor & Francis Group, 2020)
Since 2006, some Italian Regions introduced the active offer of measles, mumps, rubella, and varicella (MMRV) vaccine for all newborns during the second years of life. In 2011, Italian Drug Authority (AIFA) recommended the discontinuation of the MMRV use for an increased risk of febrile seizures following vaccination; furthermore, some Regions (such as Apulia, that introduced MMRV offer in 2009) chose to continue the use of MMRV and Ministry of Health recommended to guarantee supplemental monitoring of safety of the vaccine. In Italy, the surveillance of Adverse Events following immunization (AEFIs) is currently carried out by AIFA and Regional Health Authorities; this paper aims to summarize the results of MMRV-vaccine surveillance of AEFIs program carried out in Apulia. From the AIFA database, we selected MMRV AEFIs that occurred in Apulia (about 4,000,000 inhabitants) from 2009 to 2017. For serious AEFIs, we applied the WHO causality assessment algorithm, using for cases hospitalized information from individual medical records. In the 8 years of observation, 155 MMRV-AEFIs (reporting rate: 37.9×100,000 doses) occurred of which 26 were classified as serious (6.3×100,000 doses) and 22 led to hospitalization. Performing causality assessment, for 10 the classification was "consistent causal association to immunization" (reporting rate: 2.4×100000 doses), for 2 indeterminate, for 13 "inconsistent causal association to immunization" and for 1 not-classifiable. No case of febrile seizure resulted consistent to vaccination. All consistent serious AEFIs were completely resolved at subsequent follow-up.